Demographic, clinical characteristics and medications of rehospitalized patients for acute coronary syndrome: boomerang study - Öz, Tu?ba Kemalo?lu; Kivrak, Tarik; Almaghraby, Abdallah; Abdelnabi, Mahmoud; Tasar, Onur; Uygur, Begum; Zoghi, Mehdi (Wolters Kluwer Medknow Publications, 2021)
Background: Rehospitalizations with acute coronary syndromes (ACSs) have declined over the last years, but there is a remaining need for potential further reduction of rehospitalization after ACS to determine the most predominant predictors that can guide strategies to reduce re-hospitalizations burden. Aim: This multi-center study aimed to evaluate the demographic, clinical characteristics, and medications of rehospitalized patients who suffered a new cardiac event in 12 months after admission due to ACS. Material and Methods: Patients age >18 years who have been hospitalized between November 1 2017, and April 1 2018, for ACS within12 months before the readmission for a new acute coronary event were enrolled. Results: The present study included a total of 628 (65.9% from Turkey) consecutive patients rehospitalized with ACS (ST-elevation myocardial infarction [STEMI], 23.0%; ACS without ST-elevation [NSTE-ACS], 76.9%) from 15 different countries. The majority of the rehospitalized patients were men (67.9%), and the mean age was 63.1 ± 12.53 years. 406 (64.6%) had typical, 209 (33.2%) of patients had atypical chest pain and 13 (2.07%) had not any chest pain complaint during readmission. 304 (48.41%) of patients were discharged from hospital earlier than 3 days and 107 (17.04%) of patients stayed more than 7 days. The subcategories of first index diagnosis were 227 (36.1%) STEMI; 401 (63.8%) NSTE-ACS. The mean time from index discharge to rehospitalization was 189.25 ± 118 days. 248 (39.4%) patients were re-hospitalized more than once after index discharge. The most common risk factors were diabetes mellitus (471, 75.0%). 175 (27.87%) of patients stopped taking medication before re-hospitalization. Most of the patients (69.4%) had multivessel disease. Conclusion: Several factors identify patients at higher risk of rehospitalization with ACS. Understanding and preventing these causes can prevent rehospitalization and improve their outcome. © 2021 Society of Cardiovascular Academy. All rights reserved.
Keywords: Acute coronary syndrome; clinical characteristics; demographics; medication; rehospitalization